O papel da interação com presas e predadores na variação cromática de Gasteracantha cancriformis (Araneidae) - Gonçalves, Nathalia Ximenes (2017)
The sensory drive theory predicts that signals, sensory systems, and signaling behavior should coevolve. Variation in the sensory systems of prey and predators may explain the diversity of color signals, such as color polymorphism. The spider Gasteracantha cancriformis (Araneidae) possesses several conspicuous color morphs. The aim of the present study was to assess whether the color polymorphism of G. cancriformis may be maintained by pressure from multiple signal receivers, such as prey and predators with distinct color vision systems. In orb-web spiders, the prey attraction hypothesis states that conspicuous colors are prey lures that increase spider foraging success via flower mimicry. However, in highly defended species, conspicuous colors could also be a warning signal to predators. We used color vision modelling to estimate chromatic and achromatic contrast of G. cancriformis morphs as perceived by potential prey and predator taxa. To assess the role of prey, we conducted a prey capture experiment in the field, in which webs were assigned to four treatments: yellow, red, and black models, or no model. For each treatment, we counted the number of prey trapped on the webs and the calculated webs damaged area. To assess the role of predators on the evolution of conspicuous color patterns and polymorphism, we conducted a second field experiment, allocating yellow, red and black spider models in nylon threads along the vegetation, and observed the number of attack markings for each of them. Our results revealed that individual prey and predator taxa perceive the conspicuousness of morphs differently. Therefore, the multiple prey and multiple predator hypotheses may explain the evolution of color polymorphism in G. cancriformis. The results of prey capture experiment did not corroborate the prey attraction hypothesis nor the prey specific adaptation of color polymorphism. On the predation experiment, we found that black spider models presented more markings, which indicates that yellow and red models were less preferred, possibly suggesting that spider coloration may play a role on predator avoidance. Our results, however, do not corroborate the hypothesis that multiple predators influence polymorphism evolution. Color polymorphism in this species is possibly a multi-functional attribute, where some morphs benefits from aposematism, whereas others may alternative fitness advantages. Non-adaptive explanation should also be considered in future experiments of the evolution and maintenance of color polymorphisms.